Pengaruh Konsumsi Jantung Pisang Terhadap Peningkatan Produksi Asi Pada Ibu Menyusui di Desa Candirejo Kecamatan Biru-Biru Kabupaten Deli Serdang - Andayani Boang Manalu; Tetty Junita Purba; Nurul Aini Siagian; Mutiara Dwi Yanti (STIKes Hang Tuah Pekanbaru, 2020)
Breast milk (ASI) is the best food for babies whose nutrition is complex, and contains nutrients according to the baby's needs for growth, immunity, preventing various diseases and for the baby's intelligence. However, many mothers have problems with difficulty in getting milk out. This makes the baby not get enough milk and the mother makes the decision to give formula milk. Some mothers are afraid to breastfeed, resulting in breast milk damages because it can reduce the baby's suction at the breast causing the amount of milk to be small and not sufficient for the baby's needs. The purpose of this study was to compare the production of breast milk between the intervention group (posttest) consuming Kepok banana blossom vegetables and the control group (posttest) not to consume Kepok banana blossom vegetables in breastfeeding mothers in Candirejo Village, Biru - Biru District, Deli Serdang Regency. The method used in this study was a quasi-experimental design with a two group pretest - posttest design. The sample in this study were all breastfeeding mothers in May-July totaling 20 respondents divided into 10 respondents in the intervention group and 10 respondents in the control group. Data collection were used the observation sheet. The data were analyzed using the Wilcoxon test and then to see the comparison using the Mann Whitney test. The results showed that the mean ranks of the control was 5.65 with a sum of ranks of 56.50 increased in the intervention group with a mean ranks of 15.35 and a sum of ranks of 153.50 with a P-value of (0.000 <Î± 0, 05) then Ho is rejected, Ha is accepted. The conclusion showed that there is an effect of banana blossom consumption on increasing milk production in breastfeeding mothers in Candirejo Village, Deli Serdang Regency.